2009
DOI: 10.1103/physrevb.79.104404
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism of chromia from first-principles calculations

Abstract: The electronic structure and magnetism of chromia ͑corundum-type Cr 2 O 3 ͒ are studied using full-potential first-principles calculations. The electronic correlations are included within the LSDA+ U method. The energies of different magnetic configurations are very well fitted by the Heisenberg Hamiltonian with strong exchange interaction with two nearest neighbors and additional weak interaction up to the fifth neighbor shell. These energies are insensitive to the position of the oxygen states, indicating th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
89
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(116 citation statements)
references
References 36 publications
24
89
1
2
Order By: Relevance
“…The identification of sites A and B as the most favorable agrees with LEED measurements and molecular dynamics simulations of Ref. 6, as well as with surface x-ray diffraction data, 7 but recent LEED 10 and surface x-ray diffraction (SXRD) 11 22 the reduced coordination could make it more important at the surface. To estimate its role, we calculated the energy difference between surface models A and B in the presence of spin-orbit coupling (taking the structures relaxed without it).…”
Section: A Surface Sitessupporting
confidence: 70%
See 3 more Smart Citations
“…The identification of sites A and B as the most favorable agrees with LEED measurements and molecular dynamics simulations of Ref. 6, as well as with surface x-ray diffraction data, 7 but recent LEED 10 and surface x-ray diffraction (SXRD) 11 22 the reduced coordination could make it more important at the surface. To estimate its role, we calculated the energy difference between surface models A and B in the presence of spin-orbit coupling (taking the structures relaxed without it).…”
Section: A Surface Sitessupporting
confidence: 70%
“…Further, first-principles calculations by Rohrbach et al 16 based on the GGA+U method have shown that this termination has the lowest surface energy (compared to all others considered) over the entire range of oxygen chemical potential where Cr 2 O 3 is stable. Note that earlier results based on the GGA method, which leads to grossly incorrect electronic and magnetic properties, 22 were quite different. 15 In this work we only consider the Cr 2 O 3 (0001) surface terminated by a single layer of Cr.…”
Section: Surface Energeticsmentioning
confidence: 79%
See 2 more Smart Citations
“…Moreover, recent LSDA+U calculations 21 and combined DFT calculations with the configuration interaction method 22 pointed out the importance of electron correlation effects in the localized Cr 3d-orbitals in ruby. Even in the case of pure Cr 2 O 3 , which has less localized character compared to the impurity states, the LSDA+U calculations give great improvements for structural ground-state properties of the bulk and at surfaces [23][24][25] .…”
Section: Resultsmentioning
confidence: 99%